A rationale for including overexcitability in talent research beyond the FFM-personality dimensions. (2nd January 2021) - De Bondt, Niki; De Maeyer, Sven; Donche, Vincent; Van Petegem, Peter
ABSTRACT: The aim of this study is to provide – first theoretically and, subsequently, through an empirical analysis – a rationale for including the concept of overexcitability in talent research, beyond the five-factor model personality traits. Moreover, the empirical part of this study makes use of an innovative statistical method to address the problem of a frequentist approach to statistics in complex trait models which are based on personality questionnaire data. This study offers insight into the differential significance of overexcitability in relation to the established personality traits, emphasizing Dabrowski's dynamic approach to personality and the key contribution of overexcitability in the developmental process. Furthermore, implications for the field of giftedness are discussed.